Understanding smartphone use patterns in higher education: A latent class approach to behavioral and health risk typologies - Ramón Ventura Roque Hernández; Rolando Salazar Hernandez; Adán López Mendoza (PLoS ONE, 2025)
Introduction The widespread use of smartphones among university students has raised concern because of their potential effects and the need to detect profiles of problematic use. This study aimed to identify, characterize and differentiate different profiles of smartphone users in a sample of university students on the basis of variables such as use, nomophobia, risk and sociodemographic characteristics. Methods A total of 681 university students participated. A total of 681 university students participated in this study. The sample was recruited using a non-probabilistic, convenience sampling method. Latent class analysis -LCA- was performed to identify profiles from variables that included smartphone use patterns such as daily hours, messaging, social networks, browsing, history of technology adoption, situational use, NMPQ nomophobia questionnaire -a scale designed to assess the fear of being without a smartphone-, and reported consequences such as accidents, visual or musculoskeletal problems. The resulting classes were compared in subsequent analyses using chi-square tests for categorical variables and Mann‒Whitney U tests for ordinal variables. Results LCA revealed two clearly differentiated user profiles. Class 1 (n = 348) grouped users with moderate use and less exposure to risks and was characterized by shorter daily use of smartphones (mean = 5.46 hours), significantly lower scores on the total scale of nomophobia (mean NMPQ = 65.4 out of 140 possible points, moderate level), a lower frequency of accidents reported due to mobile use and lower reports of visual and musculoskeletal health problems. Class 2 (n = 333) grouped users with high digital involvement and multiple vulnerabilities and showed a significantly more intensive use pattern (mean = 11.01 hours per day), higher levels of nomophobia (mean NMPQ = 74.3 out of 140 possible points, moderate level), and a higher frequency of accidents and major visual and musculoskeletal health problems. Conclusion While both groups of undergraduate students could benefit from awareness and training programs, interventions could be differentiated and designed to mitigate the risks associated with problematic smartphone use. These findings provide evidence for higher education institutions and health professionals in the development of programs aimed at promoting digital well-being among university students.